2016
DOI: 10.1186/s40900-016-0031-1
|View full text |Cite
|
Sign up to set email alerts
|

Developing resources to facilitate culturally-sensitive service planning and delivery – doing research inclusively with people with learning disabilities

Abstract: Plain English summary(Please see www.Toolsfortalking.co.uk for an easy read summary of the project.) The Tools for Talking are a set of resources that were developed through collaboration between Black, Asian and minority ethnic people with learning disabilities and researchers at the University of Birmingham. The resources were designed to be used by people with learning disabilities and service providers to facilitate culturally-sensitive communication and information sharing, service planning and delivery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…A more recent special edition of a journal focussing on qualitative research (Rose & Stenfert Kroese, 2018) has highlighted the growing interest in qualitative research with this group. This includes the involvement of people with intellectual disabilities not only as qualitative research participants (e.g., Larkin, Unwin, et al, 2018;Williams, Thrift, & Rose, 2018), but also as members of the research team (Theodore et al, 2018;Unwin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A more recent special edition of a journal focussing on qualitative research (Rose & Stenfert Kroese, 2018) has highlighted the growing interest in qualitative research with this group. This includes the involvement of people with intellectual disabilities not only as qualitative research participants (e.g., Larkin, Unwin, et al, 2018;Williams, Thrift, & Rose, 2018), but also as members of the research team (Theodore et al, 2018;Unwin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Rose et al (2019) recommend researchers provide additional support when interviewing people with intellectual disabilities, such as having carers or support workers present and (as in the current study) using alternative communication approaches. Resources adapted from Unwin et al (2016) helped to facilitate the discussion and showed that it is possible to actively engage with service users who have limited verbal communication skills. Having activity-based interactions with the researcher/interviewer can help this client group to express themselves more effectively using pictures and symbols.…”
Section: Discussionmentioning
confidence: 99%
“…The semi-structured interview (Interview Schedule) was enhanced by the use of a range of techniques based on “Tools for Talking” adapted from Unwin et al (2016). This set of resources was chosen as the foundation for the development of the interview schedule with additions based on previous research with an intellectual disability population as well as a number of discussions between the authors.…”
Section: Methodsmentioning
confidence: 99%
“…The interview schedule utilized resources from "Tools for Talking" (Unwin, Larkin, Rose, Stenfert Kroese, and Malcolm (2016), developed for people with ND, specifically those with ID. Activities chosen from "Tools for Talking" allowed participants to talk about their relationships with their family members and friends, as well as identifying ideal attributes of mental health professionals and providing views about the mental health services.…”
Section: Data Collection and Analysismentioning
confidence: 99%